Oil extraction from spent coffee ground (SCG) using soxhlet extraction utilizing ethanol as solvent / Muhammad Haniff Danial Mohd Rozfaizal - Mohd Rozfaizal, Muhammad Haniff Danial (2023)
This study investigates the use of Soxhlet extraction with ethanol as the solvent to extract oil from spent coffee grounds. The effects of altering the extraction time by using cycle on the extracted oil yield were examined. The dried spent coffee ground is constant in this experiment which is 10 gram.The maximum yield of oil was produced when the extraction time was at 5 cycle. The extracted oil's composition was determined to be rich in fatty acids, making it a possible source for biodiesel production.The use of spent coffee grounds as an oil source, as well as Soxhlet extraction using ethanol as the solvent, is a sustainable and ecologically beneficial way to oil production. The Soxhlet extraction method is a simple and efficient method for extracting oil from solid materials. It was discovered that the extraction duration which using a cycle are critical elements in the oil extraction process. This research demonstrates that ethanol is an efficient solvent for extracting oil from spent coffee grounds, and that the oil recovered from coffee grounds has a high potential for use as a biodiesel feedstock.